Green curricula? An analysis of environmentally oriented curricula in economics and business administration at German institutions of higher education. (24th February 2004) - Rheinlander, Kathrin; Kramer, Matthias
The concept of sustainability is becoming more and more important as a result of growing environmental problems. Education is an essential premise to promote this concept, especially at universities and other institutions of higher education, because that is where future managers gain their education. Sustainability-oriented teaching and research is not only important in natural science, but also in economics and business administration. Companies use nature for their production by utilising resources and emitting pollutants and waste and therefore have a responsibility to respect ecological and social objectives. The purpose of this paper is to give a broad overview of the importance of environmental education in economics and business administration classes at German universities and universities of applied sciences. We have intensively analysed specific course subjects to show how to implement the concept of sustainability in economics and business courses.